Where Do I Go to Wait? Ethical Considerations During the 90 Day Reflection Period for MAiD - Disha, Kesi; Bianchi, Andria; Shanker, Ruby; Lukich, Nikolija (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2023)
Canada’s Medical Assistance in Dying (MAID) legislation changed in 2021; persons without a reasonably foreseeable natural death (RFND) could now be eligible for MAID and would have to wait at least 90 days before their intervention. This legislative change caused a new ethically complex question to arise, which we explore in this commentary, namely: Where should individuals without a RFND wait (for 90 days) in a publicly funded health system?